Literature Review: The Function of Tiktok in the 2024 Presidential Election Campaign of the Republic of Indonesia - Machsunah, Uun; Andriany, Dian (ann4publisher@gmail.com, 2024)
The 2024 Presidential Election entering January 2024 is heating up. All candidates use social media to convey their work programs. The advantages of social media as an agent of political socialization are that it can convey much information, is easily accessible, and guarantees freedom of opinion. Qualitative research methods use literature studies, and data are analyzed. The results showed that TikTok social media was an influential political socialization agent in increasing the political participation of the Indonesian people and became a means of argumentation in discussing Paslon's issues and work programs in the 2024 Presidential Election. This study concludes that TikTok social media can effectively influence political socialization through information selection and digital literacy, especially in responding to various political discourses and issues related to the 2024 Presidential Election.